Analisis Optimalisasi Pengelolaan Aset/Barang (Barang Milik Negara) di Kantor Dinas Pekerjaan Umum Provinsi Jambi - Etik Winarni; Yolanda Sari (Universitas Batanghari Jambi, 2020)
Good asset management will contribute greatly to local governments, on the contrary if the management is bad it will also have a negative impact on the local government. Based on the background above, the researcher is interested in further analyzing the